Engineered Rhizobia with Trehalose-Producing Genes Enhance Peanut Growth Under Salinity Stress - Jialin Liu; Dong Wang; Ruiqi Tong; Shengyue Ye; Yanhao Zhao; Jiangwen Wu; Yi Gan (Agronomy)
The aggravation of soil salinization has become one of the major factors that threaten crop growth and yield. Rhizobia, as an important biological nitrogen-fixing microorganism, can establish symbiotic relationships with legumes to improve their nitrogen-fixing ability and stress tolerance. Trehalose, a non-reducing disaccharide that is widely found in bacteria, fungi, and plants, can protect cellular structures and maintain the viability of cells under stress conditions. However, it remains to be determined whether the endogenous trehalose level in rhizobia could affect its stress tolerance and nitrogen-fixing capabilities. In this study, we constructed four engineered rhizobial strains to examine the effects of the overexpression and knockout of the trehalose synthesis genes otsA/otsB in the rhizobium strain CCBAU25338 on its salt tolerance and nitrogen-fixing capacity. The results indicated that the overexpression of otsA, rather than the otsB gene, significantly enhanced both the stress tolerance and nitrogen-fixing abilities of the strains. Furthermore, the inoculation of otsA-overexpressing recombinant cells leads to greater agronomic traits in the host plant’s peanuts under salinity conditions. We hope our findings may serve as valuable references for the future development of efficient and superior engineered rhizobial strains for peanut cultivation.